2022
DOI: 10.1002/advs.202105806
|View full text |Cite
|
Sign up to set email alerts
|

Functional Tumor Targeting Nano‐Systems for Reprogramming Circulating Tumor Cells with In Situ Evaluation on Therapeutic Efficiency at the Single‐Cell Level

Abstract: Tumor heterogeneity is primarily responsible for treatment resistance and cancer relapses. Being critically important to address this issue, the timely evaluation of the appropriateness of therapeutic actions at the single-cell level is still facing challenges. By using multi-functionalized nano-systems with the delivery vector composed of histone for plasmids loading, hyaluronic acid for tumor targeting, and a fusion peptide for C-X-C motif chemokine receptor 4 (CXCR4) targeting as well as nuclear localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Based on the multi-functional nano-delivery system, Ren et al realized genome editing and in situ evaluation of therapeutic response to in vitro CTCs at the single-cell level, providing accurate information for personalized cancer treatment. 157 In this study, C-X-C motif chemokine receptor 4 (CXCR4), a typical target protein in cancer therapy, was selected as the representative target for genome editing in vitro . Single cell analysis showed that CXCR4 in CTCs of cancer patients was effectively downregulated, anti-cancer biomarkers such as p53 and p21 were upregulated, and the edited cancer cells showed inhibition of proliferation and inhibition of migration and invasion.…”
Section: Downstream Analysismentioning
confidence: 99%
“…Based on the multi-functional nano-delivery system, Ren et al realized genome editing and in situ evaluation of therapeutic response to in vitro CTCs at the single-cell level, providing accurate information for personalized cancer treatment. 157 In this study, C-X-C motif chemokine receptor 4 (CXCR4), a typical target protein in cancer therapy, was selected as the representative target for genome editing in vitro . Single cell analysis showed that CXCR4 in CTCs of cancer patients was effectively downregulated, anti-cancer biomarkers such as p53 and p21 were upregulated, and the edited cancer cells showed inhibition of proliferation and inhibition of migration and invasion.…”
Section: Downstream Analysismentioning
confidence: 99%
“…Permanent disruption of oncogene by CRISPR-Cas9 gene editing offers the ability to circumvent the repetitive dosage restrictions of conventional cancer therapies, improve treatment effectiveness, and reduce therapeutic costs. , However, an essential missing link in the therapeutic translation of CRISPR editing is the creation of effective and safe delivery systems for cancer. CRISPR/Cas9 therapeutic delivery using viral and nonviral-based delivery vehicles is rapidly expanding. , However, therapeutic delivery of Cas9 protein is currently hampered by the large size of Streptococcus pyogenes , Cas9 exceeding the carrying capacity of viral and nonviral vectors . In addition, long exposure time to the Cas9 nuclease and repeated doses may raise the risk for Cas9-related immunogenicity and off-target effects. , Therefore, to reduce this risk, it is necessary to develop a delivery system that may accomplish therapeutically relevant genome editing with reduced doses and a short Cas9 exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…By using delivery vectors to deliver RNA or DNA probes into living cells, detection of nucleic acids in living cells can be realized. The vectors for RNA or DNA probes explored cover a wide range of nano-materials based on inorganic materials, organic materials, , metals, and hybrid materials. To efficiently deliver the probes into targeted cancer cells, various ligands, such as aptamers, peptides, , polysaccharides, and small molecules, were incorporated to the delivery vectors. Nevertheless, these studies are mainly focused on detection of tumor cell lines and tumor tissues of tumor bearing mice ex vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we designed biomacromolecule-based vectors for targeting delivery molecular beacons for detection of miRNA (e.g., miR-21) 26 and mRNA (e.g., CXCR4 mRNA, p53 mRNA, and p21 mRNA) 28 to CTCs. The biomacromolecule-based vectors with good biocompatibility minimize the unfavorable effects, such as perturbing RNA levels on treated cells, to ensure the accurate detection.…”
Section: ■ Introductionmentioning
confidence: 99%